A virtual factory approach for design and implementation of agile manufacturing systems - Manesh, Hamed Farahani; Schaefer, Dirk (American Society for Engineering Education, 2010)
Worldwide competition among manufacturing enterprises has acted as a driving force for the design, development and utilization of manufacturing systems with an increased degree of agility. In these regards, Holonic Manufacturing Systems (HMS) are considered an intelligent systems paradigm to meet requirements for agile manufacturing systems. Despite all advantages of HMS, design and implementation of such control systems for real industrial cases is time consuming and requires risky, but careful consideration. While some universities may be able to expose their students to the latest manufacturing systems and technologies, others may not be that fortunate due to the lack of financial resources. Because of this, alternative ways for providing their students with equivalent education and training need to be developed. A potential solution for this issue is the adoption of advanced computer technology to facilitate the provision of flexible manufacturing-related education and training programs. To date, many studies have shown that the use of computers for teaching and training purposes is feasible and rapidly becoming an integral part of the general learning process. This paper presents a Virtual Reality (VR) system tool "VR-HMS" developed for training on design of holonic manufacturing control systems to enhance the development process. The proposed VR system is a safe approach to teaching the operations of HMS, which is well known as a large-scale and complex systems for a number of operational and structural reasons. The VR-HMS allows trainees to self-experience on these systems without the need to work in actual industry. © American Society for Engineering Education, 2010.
2010 ASEE Annual Conference and Exposition --
Keywords: Competition; Control systems; Education; Engineering education; Intelligent systems; Manufacture; Personnel training; Real time systems; Students; Virtual reality; Advanced computer technology; Design and implementations; Development and utilizations; Education and training; Flexible manufacturing; Holonic manufacturing system; Large-scale and complex systems; Manufacturing enterprise; Agile manufacturing systems